Guided Endodontics in Complex Scenarios of Calcified Molars - Tavares, Warley Luciano Fonseca; Machado, VinÃcius de Carvalho; Fonseca, Francielen Oliveira; Vasconcellos, Betânia Canal; Magalhães, Luiza Cruz; Viana, Ana CecÃlia Diniz; Henriques, Luiz Carlos Feitosa (Iranian Endodontic Journal, 2020)
This study aimed to report a case series and describe the use of guided endodontics in complex symptomatic cases of mandibular and maxillary molars; presenting calcification of all three root canals. The arches of the referred patients were scanned, and high-resolution cone-beam computed tomography (CBCT) imaging was performed. Then, the taken CBCT and tooth scans were aligned and processed using software. A virtual copy of a drill was superimposed onto the scans and evaluated in 3 dimensions. Subsequently, a 3-dimensional (3D) template was designed and printed. Drilling was performed and a radiograph was taken to confirm its position. The canals were reached and endodontic treatment was performed. At the 12-month follow-up, the teeth were completely asymptomatic. The use of guided endodontics _in cases of calcification in molars_ was demonstrated to be a viable and reliable alternative treatment. The technique was based on 3D planning. Keywords: Access Opening; Apical Periodontitis; Dental Trauma; Guided Endodontics; Pulp Canal Calcification